Preliminary findings of emotion regulation in 12‐month‐old infants of mothers enrolled in a randomized controlled trial assessing a nutrition + exercise intervention. Issue 2 (7th February 2023) - Mortaji, Neda; Krzeczkowski, John; Atkinson, Stephanie; Amani, Bahar; Schmidt, Louis A.; Van Lieshout, Ryan
Abstract: Improved offspring emotion regulation (ER) has been associated with maternal intake of single nutrients or exercise during pregnancy but has not been examined in randomized trials. We investigated the impact of a maternal nutrition + exercise intervention during pregnancy on offspring ER at 12 months of age. Mothers in the Be Healthy In Pregnancy randomized controlled trial were randomly assigned to an individualized nutrition + exercise intervention plus usual care (UC) or UC alone (control group). A multimethod assessment of infant ER using parasympathetic nervous system function (high frequency heart rate variability [HF‐HRV] and root mean square of successive differences [RMSSD]) as well as maternal reports of infant temperament (Infant Behavior Questionnaire‐ Revised short form) was completed with a subsample of infants of enrolled mothers (intervention = 9, control = 8). The trial was registered at www.clinicaltrials.gov (NCT01689961). We observed greater HF‐HRV ( M = 4.63, SD = 0.50, p = .04, ƞ 2 p = .25) and RMSSD ( M = 24.25, SD = 6.15, p = .04, ƞ 2 p = .25) in infants of mothers in the intervention versus control group. Intervention group infants also had higher maternally rated surgency/extraversion ( M = 5.54, SD = 0.38, p = .00, ƞ 2 p = .65) and regulation/orienting ( M = 5.46, SD = 0.52, p = .02, ƞ 2 p = .81), and lower negative affectivity ( M = 2.70, SD = 0.91, p = .03, ƞ 2 p = .52). These preliminary results suggest that pregnancy nutrition + exercise interventions could improve infant ER but these findings require replication in larger, more diverse samples.